HUBUNGAN ANTARA KECENDERUNGAN NARSISME DENGAN MINAT MEMBELI KOSMETIK MEREK ASING PADA PRIA METROSEKSUAL - Apsari, Fitri (Universitas Sahid Surakarta, 2012)
For metrosexual men, an attractive physical appearance is one of the potential benefits for interacting with other people. Attractive appearance which leads to narcissism is supported by the cosmetic appearance of the foreign and local brands for men on the market. The hypothesis in the study that there is a correlation between narcissism tendencies with interest in buyng foreign brand cosmetics of metrosexual men. Subjects are 40 people who met at the outlets of foreign cosmetic brand with the population study as a sample collection technique. Then researcher obtained data analysis r <0.348, p = 0.014 (p <0.05). The effective contribution of 14.7%, which there are 85.3% other factors that influence the propensity of narcissism beyond cosmetics variable interest in buying foreign brands, such as psychological, biological, and sociological. There is a positive relationship between narcissism tendencies with interest in buying foreign brand cosmetics of metrosexual men.